Salivary protein concentration, flow rate, buffer capacity and pH estimation: A comparative study among young and elderly subjects, both normal and with gingivitis and periodontitis - Shaila, Mulki; Pai, G; Shetty, Pushparaj (Journal of Indian Society of Periodontology, 2013)
Background: To evaluate the salivary protein concentration in gingivitis and periodontitis patients and compare the parameters like salivary total protein, salivary albumin, salivary flow rate, pH, buffer capacity and flow rate in both young and elderly patients with simple methods. Materials and Methods: One hundred and twenty subjects were grouped based on their age as young and elderly. Each group was subgrouped (20 subjects) as controls, gingivitis and periodontitis. Unstimulated whole saliva was collected from patients and flow rate was noted down during collection of the sample. Salivary protein estimation was done using the Biuret method and salivary albumin was assessed using the Bromocresol green method. pH was estimated with a pHmeter and buffering capacity was analyzed with the titration method. Student′s t-test, Fisher′s test (ANOVA) and Tukey HSD (ANOVA) tests were used for statistical analysis. Results: A very highly significant rise in the salivary total protein and albumin concentration was noted in gingivitis and periodontitis subjects of both young and elderly. An overall decrease in salivary flow rate was observed among the elderly, and also the salivary flow rate of women was significantly lower than that of men. Conclusion: S ignificant associations between salivary total protein and albumin in gingivitis and periodontitis were found with simple biochemical tests. A decrease in salivary flow rate among elderly and among women was noted.